Blaming immigrants to enhance control: Exploring the control‐bolstering functions of causal attribution, in‐group identification, and hierarchy enhancement. (18th May 2021) - Hirsch, Magdalena; Veit, Susanne; Fritsche, Immo
Abstract: Blaming immigrants seems to be in part motivated by the need for control. However, three alternative explanations have been proposed as to why blaming bolsters feelings of control. First, blaming may restore a sense of an orderly world in which negative events can be attributed to a clear cause (causal attribution). Second, blaming others may strengthen in‐group identities thereby facilitating group‐based control (in‐group identification). Finally, blaming low‐status groups may enhance individuals' perceptions of dominance and superior status (hierarchy enhancement). Addressing these arguments, we conducted two survey experiments in the German context. In the first experiment, we examined the control‐bolstering functions of causal attribution and in‐group identification. Participants were primed with an economic crisis threat and then, given the opportunity to either blame out‐groups (immigrants and managers), blame an abstract cause (globalization), or affirm their national identity. In the second experiment, we examine control enhancement in the context of political conflict and status hierarchies. Participants had the opportunity to either express prejudice toward low‐status out‐groups (immigrants and obese people) or indicate their opinion on the polarized issue of representation of the far‐right. Both studies replicate earlier findings showing that anti‐immigrant blaming and prejudice enhances the feelings of control. Neither mere causal attribution nor mere in‐group identity salience produce similar control‐bolstering effects. Instead, findings suggest that intergroup conflict and status differences benefit control the enhancement processes supporting accounts of both group‐based control and social dominance. Findings are discussed with respect to social cohesion and the appeal of populist frames promoting antagonistic, unequal intergroup relations.